Quality Control in Plastic Injection Manufacturing at PT. Minebea Accesssolution Indonesia The Number of NG Scratch - Aziz, Khaerul; Pranata, Juan; Alam, Ihsan Cahya; Ramadhani, Fajri; Burhanudin, Ahmad Zaky; Prastyo, Yudi (Lentera Ilmu Nusantara, 2025)
The company is critical in quality, namely a lot of NG (Not Good) is sent to the Assembly, the type of NG (Noot Good) that is sent a lot is NG (Scracth) in the TG1 R/L Base part affects the cycle time in the production process on the assembly line to analyze and find out the root cause of the problem, we use 4M (Man, Machine, Method, Material) analysis and PDCA silkus. It was found that the root of this problem is the lack of implementation of 1 QC Inplant that understands the standard quality of products in plastic injection manufacturing, dirty dies, lack of maintenance of dies (molds) and the existence of a high workload which was originally the number of machines operated by 1 operator 2 machines, now it is 4 machines 1 operator, so there is a lack of operator time in checking the product, Before the repair of defective products reached 25%/month and the yield decreased to 8%/boaln after implementing the repair. The improvement steps include, the addition of 1 QC inplant who understands the quality standards on the product, the addition of check seet cleaning dies, and further training to machine operators. This study concluded that the improvement was effective even though it was not 100%, in identifying and controlling factors that affect quality in the production process in each shift.